KALIMAT IMPERATIF DALAM BAHASA INGGRIS DAN BAHASA PONOSAKAN (SUATU ANALISIS KONTRASTIF) - Turang, Giovana Gina; Kodong, Fentje; Rattu, Jultje A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT This research entitled ?Kalimat Imperatif dalam Bahasa Inggris dan Bahasa Ponosakan? and focuses on the types, functions, similarities, and differences of imperative sentences in English and Ponosakan language. The writer arranged some questions for this research, that are: what are the types and functions, and the similarities and differences of imperative sentences in English and Ponosakan language.The data in English were collected by reading and studying as many references as possible related to this research. The data in the Ponosakan language was taken from 3 informants who know well about the Ponosakan language and used it in their daily conversations. After collecting the data, the writer identified and classified the imperative sentences in English and Ponosakan language. After that, the data were analyzed by using the contrastive analysis method. The writer contrasted the data between English and Ponosakan language to find the similarities and differences. Imperative sentences in English and Ponosakan language are devided into types and functions. The types are imperative sentences with subject, imperative sentences without subject, imperative sentences with let us, negative imperative sentences, and imperative sentences with do. The functions of imperative sentences in English and Ponosakan language are command, wish, invitation, and warning.Keywords: imperative sentences, English and Ponosakan Language, contrastive analysis.